Experimental and numerical studies on the impact resistance of reinforced concrete-steel liner composite targets subjected to the tube-type missile impact - Delei Zou; Bo Liu (Case Studies in Construction Materials, 2025)
This study investigates the dynamic response, damage mechanisms and strategies for enhancing the resistance of reinforced concrete-steel liner (RC-SL) composite structures subjected to tube-type missile impacts. Experimental tests were conducted on eight RC-SL specimens with varying configurations using a large-caliber single-stage gas gun. Finite element (FE) models were developed and validated against experimental data, accurately predicting displacement, acceleration, and damage patterns, though minor limitations in capturing localized failures were noted. The study identified characteristic damage patterns of RC-SL composite structures, including front-side craters, rear-face spalling, tensile tearing, bulging, and localized buckling. Design optimizations, such as rear-mounted steel liners and welded stud-rebar mesh, were found to enhance energy dissipation and interfacial load transfer. The validated finite element (FE) model was utilized to evaluate the safety of a 1.6 × 105 m³ LNG storage tank dome under industry-standard missile impact scenarios. The analysis confirmed that a 400 mm-thick dome sustains only localized damage, with penetration depths varying between 30 and 160 mm, surface crater diameters ranging from 10 to 50 mm, and rear collapse area diameters spanning from 500 to 900 mm. These results demonstrate that the dome maintains both structural integrity and air tightness under such threats. The research conclusions and analytical methods establish a robust foundational framework for the design and failure analysis of RC-SL protective structures, enhancing the reliability of engineering applications.